[AR] Ta’limiyyah al-Lughah al-‘Arabiyyah wa Ishkalat al-Manahij al-Tarbawiyah: Madamin al-Kitab al-Madrasi Unmuzajan: Teaching of Arabic Language and Issues of Educational Syllabus: The Contents of the Textbook as Case Study (Afaq Lughawiyyah, 2024)
The promotion of the learning of Arabic by both native and non-native speakers can’t be reached without the use of scientific research applications, the investment of significant research efforts, the application of pedagogical projects and the use of various electronical applications. In fact, the most important role of scientific research and its various applications resides in the challenges, identifying. The issues and applying a little constructive criticism so as to improve its learning according to the suitable pedagogical model that aims at realizing the objectives of the educational program and society’s general project. This sheet of paper takes part of the challenges and issues that scientific research faces in the domain of teaching the Arabic language. It aims at identifying some of the difficulties that individuals who are working in the department of teaching the Arabic face. It also suggests some possible solutions.  And it takes from the contents of the textbook and educational curricula a model for the most important of these issues. As it seeks to question the Arabic language textbook by virtue of its presence at the heart of the educational learning process and in the depth of the pedagogical relationship, to what extent it responds to the learner's requirements as well as their cognitive, educational, and emotional expectations. With a discussion about the expected outcomes from the textbook and anticipating its new horizons.